Co-expression of Cyanobacterial Genes for Arsenic Methylation and Demethylation in Escherichia coli Offers Insights into Arsenic Resistance - Yan, Yu; Xue, Xi-Mei; Guo, Yu-Qing; Zhu, Yong-Guan; Ye, Jun (Frontiers in Microbiology, 2017)
Arsenite [As(III)] and methylarsenite [MAs(III)] are the most toxic inorganic and methylated arsenicals, respectively. As(III) and MAs(III) can be interconverted in the unicellular cyanobacterium Nostoc sp. PCC 7120 (Nostoc), which has both the arsM gene (NsarsM), which is responsible for arsenic methylation, and the arsI gene (NsarsI), which is responsible for MAs(III) demethylation. It is not clear how the cells prevent a futile cycle of methylation and demethylation. To investigate the relationship between arsenic methylation and demethylation, we constructed strains of Escherichia coli AW3110 (ΔarsRBC) expressing NsarsM or/and NsarsI. Expression of NsarsI conferred MAs(III) resistance through MAs(III) demethylation. Compared to NsArsI, NsArsM conferred higher resistance to As(III) and lower resistance to MAs(III) by methylating both As(III) and MAs(III). The major species found in solution was dimethylarsenate [DMAs(V)]. Co-expression of NsarsM and NsarsI conferred As(III) resistance at levels similar to that with NsarsM alone, although the main species found in solution after As(III) biotransformation was methylarsenate [MAs(V)] rather than DMAs(V). Co-expression of NsarsM and NsarsI conferred a higher level of resistance to MAs(III) than found with expression of NsarsM alone but lower than expression of only NsarsI. Cells co-expressing both genes converted MAs(III) to a mixture of As(III) and DMAs(V). In Nostoc NsarsM is constitutively expressed, while NsarsI is inducible by either As(III) or MAs(III). Thus, at low concentrations of arsenic, NsArsM activity predominates, while NsArsI activity predominates at high concentrations. We propose that coexistence of arsM and arsI genes in Nostoc is advantageous for several reasons. First, it confers a broader spectrum of resistance to both As(III) and MAs(III). Second, at low concentrations of arsenic, the MAs(III) produced by NsArsM will have antibiotic-like properties and give the organism a competitive advantage. Finally, these results shed light on the role of cyanobacteria in the arsenic biogeochemical cycle.